Pengamanan M-Commerce Menggunakan One Time Password Metode Pseudo Random Number Generator (PRNG) - Muhammad Fahrizal; Achmad Solichin (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2020)
Mobile commerce or m-commerce is an electronic trading system (e-commerce) that uses mobile equipment such as mobile phones, smart phones, PDAs, and notebooks. With the growth of smartphone users throughout the world, many electronic commerce business owners also provide m-commerce applications to make it easier for their customers to make transactions. In addition to providing convenience for users, m-commerce application providers must be able to ensure that customers can transact safely. Security risks are one of the major obstacles in the development of electronic commerce systems. Therefore, this research applies the method of securing m-commerce applications using one time password (OTP) generated by the Pseudo Random Number Generator (PRNG) method. This study also modified the PRNG algorithm by doing three bit shifting processes and adding encryption algorithms. The test results show that the system can generate an OTP that is always unique for each transaction. The results of this study are useful for m-commerce application developers to secure their applications.